News Translation Strategies - Hernández-Guerrero, María José (Routledge, 2022)
News translation generates texts that clearly deviate from what would traditionally be considered faithful and accurate translations of the original. This reality has attracted the attention of the academic world and numerous studies have focused on the analysis and description of the transformations that translated news goes through, showing the different strategies used to adapt the original news stories to the functional and ideological needs of the receiving news company and the new audiences. The sociological implications of this state of affairs are obvious: a significant portion of the news stories circulating on a global scale are translated news which plays a role in moulding the recipients’ opinions, actively influencing the way in which they perceive the world around them. Hence the importance of knowing what mechanisms the media use to translate information, why they use them and with what results. This chapter attempts to provide an overview of the strategies which allow the journalist-translators to reshape the source texts to cater to the needs and interests of the foreign readers and to comply with the target news companies’ ideological stances. With this aim in mind, we will focus on the principal processes involved in news translation; and review the main strategies applied both at macrotextual and microtextual levels as well as those used on specific elements in the news story such as headlines and quotes. Finally, we will present the latest advances in this field.
https://www.routledge.com/our-products/open-access-books/publishing-oa-books/chapters?srsltid=AfmBOorJiXxoaFVhr5A0CfGfEUW4JpZnzDO2qyyFAnMk2F2bcXLR_dAq
Keywords: Periodismo - Traducción; Journalistic translation; Traducción periodística; Técnicas de traducción; Translation Strategies; News translation